Neglected Non-Communicable Diseases-Looking beyond the BIG FOUR - Bhattacharya, Sudip; Bera, Om Prakash (Indian Journal of Community Health, 2022)
In the era of Sustainable Development Goal, we have gone to the next level for achieving SDGs by monitoring and evaluation of SDG indexes,(1) still we conceptualize that public health will face newer challenges in healthcare (SDG-3) in the form of Neglected Non-Communicable Diseases (NNCD) in the near future.(2) Poor nations are already facing the heat of double burden of communicable and non-communicable illnesses (NCDs), often known as chronic illnesses, which are characterized by a protracted course and are multifactorial in causation.(3) Cardiovascular disorders, Cancers, Chronic Respiratory Diseases, and Diabetes are considered as the most common NCDs entitled as BIG FOUR. NCDs disproportionately impact persons in poor countries, where almost three-quarters (31.4 million) of all NCD-related fatalities occur. (2,4–6) The "BIG FOUR" NCDs (cardiovascular diseases, malignancies, chronic respiratory illnesses, and diabetes) are well-recognized as the leading causes of global health loss, in terms of morbidity and mortality. However, 55 percent of the worldwide burden of NCDs is caused by other NCDs, which are often overlooked in terms of increased premature mortality, increased Disability Adjusted Life Years (DALY) and reduced Quality-Adjusted Life Year (QALY). The share of disease burden caused by “Cancer, COPD, Cardiovascular disease, and Diabetes-the BIG FOUR” is the greatest among all NCDs. However, many additional non-communicable diseases cause a comparable fraction of disease burden but receive less attention than the "BIG FOUR."(2,6)